Circumstantial evidence -The standard of proof required in criminal cases / Ahmad Khairi Khairuddin - Khairuddin, Ahmad Khairi (Faculty of Law, 1984)
This paper primarily deals with the standard of proof in criminal cases where the evidence against the accused is wholly circumstantial. The first chapter is the introduction to the Paper. In that chapter, the distinctions between direct, indirect and circumstantial evidence are laid out* The second chapter deals with the principle as enunciated by Alderson B. in R.v.Hodge in where the evidence against the accused is wholly circumstantial, the jury must be satisfied not only that those circumstances were consistent with his having committed the act, but they must also be inconsistent with any other material conclusion than that the prisoner was the guilty person. That direction was followed by earlier Malaysian cases- In that chapter too, the relationship between circumstantial evidence and corpus delicti is also discussed. Chapter III deals with the case of McGreevy v. Director of Public Prosecutions which held that no such special direction is required. The chapter also features the criticisms made against McGreevy's case by the Australian and New Zealand courts. The position adopted by the Malaysian Courts after McGreevy's case is also discussed. Chapter IV inter alia deals with the case of Jayaraman & Ors v. Public Prosecutor which followed McGreevy«s case. The "irresistible conclusion test" as stated by Othman P.J.